Regulation of Electronic System-Based Trade in the Framework of the ASEAN Economic Community and its Implications for Indonesia - Sommaliagustina, Desi; Daulay, Zainul; Delfiyanti, Delfiyanti; Elvardi, Jean (Fakultas Syariah Institut Agama Islam Negeri Lhokseumawe, 2025)
Electronic trading (PMSE) facilitates transactions, both nationally and internationally. This study aims to examine PMSE regulations within the scope of the ASEAN Economic Community (AEC) and their impact on consumers in Indonesia. This study employs a normative legal method with a descriptive-prescriptive approach. Data collection was conducted through literature review, while data analysis was performed descriptively. The results of the study reveal that PMSE regulations in ASEAN are governed by the ASEAN Blueprint, the ASEAN Charter, and the ASEAN Agreement on E-Commerce (AAEC). The AAEC consists of 19 articles, covering various aspects such as cooperation mechanisms and scope, facilitation of cross-border electronic commerce, cybersecurity, digital payment systems, logistics, transparency, dispute resolution, and agreement implementation. These regulations aim to strengthen cross-border trade in ASEAN, create a business environment that supports Small and Medium Enterprises (SMEs), and strengthen cooperation among member countries to accelerate inclusive economic growth and reduce disparities in the region. Regarding the impact of the ASEAN trade agreement on Indonesian consumers following the implementation of Law No. 4 of 2021, it was found that there are still other national regulations governing e-commerce, including the Electronic Information and Transactions Law (EIT Law), the Trade Law, and Government Regulation No. 82 of 2012 on the Implementation of Electronic Systems and Transactions.